Morphological marking of contrast in Tima. Issue 1 (28th December 2020) - Becker, Laura; Schneider-Blum, Gertrud
Abstract : Tima (Niger-Congo, Sudan) has two morphological means to express contrast: focus marking and selective marking. We take the distribution of both marking options and their interaction as evidence for a broad approach to contrast, the latter being a gradient phenomenon rather than a categorical one. We show for Tima that exhaustivity and unexpectedness play a role in determining the strength of the contrast, with the selective marker and focus marker occurring with weaker and stronger types of contrast respectively. While the selective marker signals the existence of a set of alternatives singling out one alternative, the focus marker requires that the information under focus is either exhaustive or unexpected.